Targeting SLC22A5 fosters mitophagy inhibition-mediated macrophage immunity against septic acute kidney injury upon CD47-SIRPα axis blockade - Yu Jia; Jun-Hua Li; Bang-Chuan Hu; Xia Huang; Xi Yang; Yan-Yan Liu; Juan-Juan Cai; Xue Yang; Jun-Mei Lai; Ye Shen; Jing-Quan Liu; Hai-Ping Zhu; et al. (Heliyon, 2024)
Efferocytosis of apoptotic neutrophils (PMNs) by macrophages is helpful for inflammation resolution and injury repair, but the role of efferocytosis in intrinsic nature of macrophages during septic acute kidney injury (AKI) remains unknown. Here we report that CD47 and signal regulatory protein alpha (SIRPα)—the anti-efferocytotic ‘don't eat me’ signals—are highly expressed in peripheral blood mononuclear cells (PBMCs) from patients with septic AKI and kidney samples from mice with polymicrobial sepsis and endotoxin shock. Conditional knockout (CKO) of SIRPA in macrophages ameliorates AKI and systemic inflammation response in septic mice, accompanied by an escalation in mitophagy inhibition of macrophages. Ablation of SIRPA transcriptionally downregulates solute carrier family 22 member 5 (SLC22A5) in the lipopolysaccharide (LPS)-stimulated macrophages that efferocytose apoptotic neutrophils (PMNs). Targeting SLC22A5 renders mitophagy inhibition of macrophages in response to LPS stimuli, improves survival and deters development of septic AKI. Our study supports further clinical investigation of CD47-SIRPα signalling in sepsis and proposes that SLC22A5 might be a promising immunotherapeutic target for septic AKI.